Analysis of Risk Factors for the Occurrence of Diabetic Foot Ulcers in Patients with Type II Diabetes Mellitus - Kaylan Wesle Elian; André Athrison; Stephany Daleska Cielo; FIrolella Camia Angelo; Barbara Cathrine Nichole; Asmat Burhan; Indah Susanti (Journal of Wound Research and Technology, 2024)
Background: Diabetes Mellitus (DM) has become a prevalent disease, imposing a significant burden on public health due to its widespread occurrence and association with numerous disabilities and fatalities. Uncontrolled DM can lead to severe metabolic complications and long-term vascular issues, including microangiopathy and macroangiopathy. Additionally, individuals with DM are highly susceptible to foot infections, which can escalate into gangrene if not properly managed. Purpose: This study aimed to determine the risk factors for diabetic foot ulcers in patients with Type II Diabetes Mellitus at the Hospital Infatil e Maternidade Jardim Amalia Methods: The research employed an analytical survey method with a case-control study design. Purposive sampling was utilized to select a total of 134 participants, comprising 67 individuals in the case group (those with diabetic foot ulcers) and 67 in the control group (those without diabetic foot ulcers). Data collection was conducted using a structured questionnaire, and the results were analyzed using the Odds Ratio (OR) test to identify significant risk factors. Findings: The findings of the study indicated that age is a risk factor for developing diabetic foot ulcers in patients with Type II DM, with an OR of 3.15 (95% CI: 0.43-17.216). The duration of diabetes also emerged as a significant risk factor, with an OR of 3.13 (95% CI: 0.62-14.12). Furthermore, foot care practices were identified as a crucial risk factor, with an OR of 4.13 (95% CI: 0.72-12.45). Conclusion: this study demonstrates that age, the length of time a patient has had diabetes, and their foot care routines are significant risk factors for the development of diabetic foot ulcers in patients with Type II Diabetes Mellitus at Hospital Infatil e Maternidade Jardim Amalia. These findings underscore the importance of early intervention and targeted patient education to mitigate these risks and improve patient outcome